2012
DOI: 10.1002/cphc.201200789
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Carbon Nano‐Onion/PEDOT:PSS Composites

Abstract: Composites of unmodified or oxidized carbon nano-onions (CNOs/ox-CNOs) with poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) are prepared with different compositions. By varying the ratio of PEDOT:PSS relative to CNOs, CNO/PEDOT:PSS composites with various PEDOT:PSS loadings are obtained and the corresponding film properties are studied as a function of the polymer. X-ray photoelectron spectroscopy characterization is performed for pristine and ox-CNO samples. The composites are characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 100 publications
0
35
0
Order By: Relevance
“…In general, PANI films containing carbon nanostructures showed improved properties like a lower resistance and higher mechanical stability than pure PANI films. Another CNO-containing composite material was prepared from unmodified or oxidized CNOs and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) [47]. In a very recent study, they reported the non-covalent functionalization of CNOs with poly(4-vinylpyridine- co -styrene) (PVPS) and poly(ethylene glycol)/Polysorbate 20 (PEG/P20) [48].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, PANI films containing carbon nanostructures showed improved properties like a lower resistance and higher mechanical stability than pure PANI films. Another CNO-containing composite material was prepared from unmodified or oxidized CNOs and poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) [47]. In a very recent study, they reported the non-covalent functionalization of CNOs with poly(4-vinylpyridine- co -styrene) (PVPS) and poly(ethylene glycol)/Polysorbate 20 (PEG/P20) [48].…”
Section: Reviewmentioning
confidence: 99%
“…After optimization in a follow-up study, the highest specific capacitance for a CNO–PANI composite was measured to be 525 F·g −1 , which renders this composite material interesting for applications in supercapacitor electrodes [46]. Also the CNO/PEDOT:PSS composites, which were previously discussed, showed promising properties for the application as electrode material in supercapacitors, such as a specific capacity of 96 F·g −1 , good cation-exchange properties and a simple synthesis [47]. In a recent study, the same group decorated the surface of CNO with Ni(OH) 2 or NiO as pseudocapacitive redox material and showed that these composites can be promising materials for the development of supercapacitors [61].…”
Section: Reviewmentioning
confidence: 99%
“…53 For the preparation of the lms a conductive carbon paste was used to solubilize the non-modi-ed and modied CNOs for further modication of the GC surface electrodes. As was previously observed, the capacitive performance of the carbon electrodes depends on their preparation protocol.…”
Section: Morphology Characterization and Electrochemical Studiesmentioning
confidence: 99%
“…Although PEDOT has electrical conductivities two or three magnitudes higher than polyaniline, its thermal stability is limited up to 180 °C. To overcome this inconvenience many authors have attempted to dope PEDOT and other conductive polymers with nanostructured clays, silico‐aluminates, metal or metal oxides nanoparticles . Gabaldón et al synthesized PEDOT over halloysite nanotubes (HT).…”
Section: Introductionmentioning
confidence: 99%